The relics of Columbus : an illustrated description of the historical collection in the monastery of La Rabida - Curtis, William Eleroy, 1850-1911 (W.H. Lowdermilk Co., 1893)
Catalogue of the exhibit on Christopher Columbus shown in the replica of La Rábida at the World's Columbian Exposition in 1893.